2020
DOI: 10.20849/ijsn.v5i3.765
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Efficiency Analysis of Share Decision Making in the Atrial Fibrillation Patients

Abstract: Background: Atrial Fibrillation (AF) prevalence rate is about 2%-3% worldwide. The risk of stroke in patients with AF is 4 -5 times than normal. It’s important to take oral anticoagulant therapies to prevent stroke.Aims: The purpose of this study was to estimate whether share decision making (SDM) could lower the anxiety and improve the intension of medical decision or not.Methods: This was one-group pretest-posttest study design. The study contained 21 patients who had hospitalized following diagnosis and tre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 6 publications
1
0
0
Order By: Relevance
“…Cheng et al found that anxiety decreased from 3.5 points to 2.1 points (p < 0.05) in patients with AF using SDM [15], which is consistent with the present study showing that SDM can reduce patients' anxiety. Our study showed that the willingness to use medication increased from 76.9% to 88.5% in AF patients with SDM.…”
Section: Influence Of Sdm On Patients' Decision Makingsupporting
confidence: 92%
“…Cheng et al found that anxiety decreased from 3.5 points to 2.1 points (p < 0.05) in patients with AF using SDM [15], which is consistent with the present study showing that SDM can reduce patients' anxiety. Our study showed that the willingness to use medication increased from 76.9% to 88.5% in AF patients with SDM.…”
Section: Influence Of Sdm On Patients' Decision Makingsupporting
confidence: 92%